Evaluating the Perceived Effectiveness of Online Learning Tools for English language in Hard-to-ReachAreas - Dr. Nazia Habib , Dr. Sheheryar Naveed , Dr. Shoaib Akhter , Dr. Momna Yousaf (Migration Letters, 2024)
This study assessed the effectiveness of online learning systems introduced in Higher Education Institutions for teaching English language courses in Khyber Pakhtunkhwa province of Pakistan. The objective was to identify the loopholes and issues faced by students of hard-to-reach areas and to assess their level of satisfaction with the online learning system in comparison to traditional classroom learning methods. Cross-sectional data were collected from 270 students from seven randomly selected universities through an online survey, using adapted questionnaires. Data were analyzed using descriptive and comparative analytical techniques. The results indicated that classroom systems were perceived as more effective than online systems for learning English language in Khyber Pakhtunkhwa province of Pakistan, mainly because of ineffective learning technology and unconducive learning environments for online education. This study has important implications for stakeholders and policymakers.